2018
DOI: 10.1016/j.jcin.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Direct Transcatheter Aortic Valve Replacement Without Balloon Aortic Valvuloplasty on Procedural and Clinical Outcomes

Abstract: We confirmed that TAVR without BAV is frequently performed in France with good procedural results. This procedure is associated with procedural simplification and lower rates of residual aortic regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
3
38
0
2
Order By: Relevance
“…Multiple TF-TAVI studies have found procedural durations to be significantly shorter in the absence of predilation, with reported times of 50.5–133.7 min where BAV is performed compared with 34.0–108.7 min when it is not 6 7 17–20. Concurrently, omission of BAV in the present study resulted in procedural times that were an average of 34 min shorter, as well as reduced fluoroscopy times, confirming its time-saving advantage.…”
Section: Discussionsupporting
confidence: 77%
“…Multiple TF-TAVI studies have found procedural durations to be significantly shorter in the absence of predilation, with reported times of 50.5–133.7 min where BAV is performed compared with 34.0–108.7 min when it is not 6 7 17–20. Concurrently, omission of BAV in the present study resulted in procedural times that were an average of 34 min shorter, as well as reduced fluoroscopy times, confirming its time-saving advantage.…”
Section: Discussionsupporting
confidence: 77%
“…Multivariate analysis found postdilatation a significant predictor for brain lesions, whereas predilatation and VIV procedure itself turned out to be none‐significant predictors. Predilatation was the operator's discretion, performed in a rate comparable with the common practice . The main reason to postdilate was the presence of a significant paravalvular leak.…”
Section: Discussionmentioning
confidence: 99%
“…The geriatric population has grown, leading to an increased number of patients undergoing TAVR. Taking this epidemiological fact into consideration, improve- ments in transcatheter technology and increased operator experience leading to further simplification of the procedure are key to achieving the best result in such a fragile population [6,7]. According to recent data, the incidence of periprocedural complications defined by the Valve Academic Research Consortium may be similar between the different age groups [4].…”
Section: Incidence Of Age-associated Complications and Impact Of Incrmentioning
confidence: 99%
“…Balloon aortic valvuloplasty can improve annular sizing, facilitate the delivery system passing through the stenotic native valve, and is supposed to optimize valve expansion [7,17]. Nevertheless, BAV has been related to hemodynamic instability, acute aortic regurgitation, renal failure, increased incidence of stroke, and pacemaker implantation [7,[18][19][20].…”
Section: Incidence Of Age-associated Complications and Impact Of Incrmentioning
confidence: 99%